Appetitive to aversive counter‐conditioning as intervention to reduce reinstatement of reward‐seeking behavior: the role of the serotonin transporter - Karel, Peter; Almacellas‐Barbanoj, Amanda; Prijn, Jeffrey; Kaag, Anne‐Marije; Reneman, Liesbeth; Verheij, Michel M.M.; Homberg, Judith R. (Addiction biology, 2019)
Counter‐conditioning can be a valid strategy to reduce reinstatement of reward‐seeking behavior. However, this has not been tested in laboratory animals with extended cocaine‐taking backgrounds nor is it well understood, which individual differences may contribute to its effects. Here, we set out to investigate the influence of serotonin transporter (5‐HTT) genotype on the effectiveness of counter‐conditioning after extended access to cocaine self‐administration. To this end, 5‐HTT+/+ and 5‐HTT−/− rats underwent a touch screen‐based approach to test if reward‐induced reinstatement of responding to a previously counter‐conditioned cue is reduced, compared with a non‐counter‐conditioned cue, in a within‐subject manner. We observed an overall extinction deficit of cocaine‐seeking behavior in 5‐HTT−/− rats and a resistance to punishment during the counter‐conditioning session. Furthermore, we observed a significant decrease in reinstatement to cocaine and sucrose associated cues after counter‐conditioning but only in 5‐HTT+/+ rats. In short, we conclude that the paradigm we used was able to produce effects of counter‐conditioning of sucrose seeking behavior in line with what is described in literature, and we demonstrate that it can be effective even after long‐term exposure to cocaine, in a genotype‐dependent manner. Typical extinction training is insufficient to prevent reinstatement of drug seeking in laboratory animals. Here, we describe a touch screen‐based counter‐conditioning procedure that is designed to reduce reward induced reinstatement in wild‐type (5‐HTT+/+) and serotonin transporter knockout rats (5‐HTT−/−) after extended access to cocaine or sucrose self‐administration. Our results suggest that the procedure was able to reduce reward induced reinstatement in 5‐HTT+/+ but not in 5‐HTT−/− rats.